Survival rate of the Hall technique compared with resin composite restoration in multi-surface cavities in primary teeth: a 1-year randomized clinical trial (Journal of Applied Oral Science, 2023)
Background: Hall technique (HT) has been indicated for teeth with dentinal caries lesion; however, extensive cavities, with more than two surfaces still seem challenging for restorative treatment in pediatric dentistry, resulting in a higher failure rate and an increased need for retreatment. Objectives: To compare the survival rate of the Hall technique preformed metal crown (HT) with resin composite restoration (RC) for multi-surface cavitated caries lesions in primary molars. Methodology: In this multicenter two-arm randomized clinical trial, children between 4 and 9 years of age with at least one primary molar with cavitated caries lesion involving more than two surfaces, including one buccal or palatal/lingual surface, were selected from 17 Brazilian cities. A total of 364 teeth were allocated into two groups: (1) teeth treated with selective caries removal and RC and (2) treated with the HT. The survival rate was assessed at 6 and 12 months after the interventions. Survival analysis was performed with the Kaplan‒Meier method. Cox regression was used to determine the influence of explanatory variables on the survival rate (α=5%). Results: After 12 months, 292 teeth were re-evaluated. A total of 358 teeth were re-evaluated at least once during the study and included in the survival analysis. The HT (87.8%) resulted in a higher survival rate than RC restoration (75.7%) (p=0.004). Conclusion: HT has a higher survival rate than RC as a treatment for multi-surface cavitated caries lesions in primary teeth. ClinicalTrials.gov: NCT02782390